Selection and Surface Modifications of Current Collectors for Anode-Free Polymer-Based Solid-State Batteries - Garcia-Calvo, Oihane; Gutiérrez-Pardo, Antonio; Combarro, Izaskun; Orue, Ander; Lopez-Aranguren, Pedro; Urdampilleta, Idoia; Kvasha, Andriy (Frontiers in Chemistry, 2022)
Anode-free batteries (AFB) have attracted increasing interest in recent times because allow to eliminate the conventional anode from the cell, exploiting lithium inventory from a lithiated cathode. This implies a much simpler, cost-effective, and sustainable approach. The AFB configuration with liquid electrolytes is being explored widely in research, but rarely using solid electrolytes. One of the main issues of AFB is the poor reversibility of lithium plating/striping process at the anode side. Therefore, in this work, different metal foils have been tested as anode current collectors (CC), and copper foil has been selected as the most promising one. Surface modifications of the selected copper foil have been performed by its coating using composite layers made of carbon and different metal nanoparticles - such as Ag, Sn, or Zn - in different proportions, and with different amounts of binder. The impact of such coatings and their thickness on the electrochemical performance of single layer solid-state anode free pouch cells, based on a PEO electrolyte and a LiFePO4 cathode, has been systematically studied. Consequently, a post-mortem analysis of the investigated solid-state AFB is also presented, trying to identify and elucidate possible failure mechanism to enhance the electrochemical performance of solid-state AFB in future.